United States military working dogs from 2019 to 2021: analysis of causes of service discharge and decreased service life - Discepolo, Dakota; Farr, Brian; Broach, Desiree; Henderson, Andrea; Gerardo, Angelina; Dyer, Jessie; Best, Eric (Frontiers in Veterinary Science, 2025)
IntroductionMilitary working dogs (MWDs) are maintained by the United States Department of Defense (DoD) in effort to maintain readiness. MWDs provide valuable abilities which include explosive and drug detection capabilities as well as security support. However, acquiring, training, and maintaining MWDs requires significant investment of resources. Therefore, understanding the prominent causes of service discharge and associated causes and demographics associated with decreased service duration in the modern MWD population is crucial.MethodsTo meet this objective, an extensive review was conducted of service discharge records of MWDs who were discharged from service in fiscal years 2019 through 2021. The causes of service discharge were categorized and subcategorized by Army Veterinary Corps Officers with extensive MWD experience. Service life and operational service life were calculated using lifecycle dates. Chi-square analysis compared frequencies of categories and subcategories, and logistic regression analysis was conducted on occurrence of the five most prominent categories to identify associations with breed, size, subpopulation, goal at procurement, outcome of service discharge, and duration of service.ResultsThe presented results include data on 1,230 MWDs who were discharged from service during the selection period. The five most prominent causes of service discharge were neuromusculoskeletal disease, training, fear-anxiety, neoplasia, and heat injury which accounted for discharge of 83.50% of the MWDs. Each of these prominent categories were significantly associated with at least one of the population characteristics analyzed and all of them were significantly associated with duration of service. ANOVA analysis comparing mean service life resulted in significant differences of mean overall service with main effects of breed (p = 0.0252), outcome (p = 0.0004), service discharge category (p < 0.0001), and subpopulation (p < 0.0001).ConclusionThese findings can inform mitigation strategies to prevent early or preventable service discharge in the future.